METHOD OF DESCRIPTION OF THE PURPOSE AND ESSENCE OF THE TOPIC IN TEACHING PHYSICS - Meliyev F.; Abduraxmonov M.; Ikromov A.; Zoirov S.X., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article talks about the content of educational work carried out during the organization of a folklore club and training, as well as the possibilities of learned songs for educating young people in the spirit of national values.